Case Report: Ring chromosome 21 and craniofacial malfomation - Briceno, Ignacio; Martínez, Julio Cesar; Brigmon, Mathew; Arias, Liliana; Venegas, Adriana (Iatreia, 2010)
<div style="color: #000000; font-family: Verdana, Arial, Helvetica, sans-serif; font-size: 10px; background-image: initial; background-attachment: initial; background-origin: initial; background-clip: initial; background-color: #ffffff; margin: 8px;"> We report a case of a feminine child who is the product of a second controlled pregnancy ended preterm (36 weeks) by cesarean delivery, who also incurred a premature rupture of membranes. At birth, the child weighed 2100g, height of 47cm, she was diagnosed early with an atrial septal defect which required several hospital stays until surgical correction at 4 years of age. During surgical corrections, a small cyst was found posterior to the common bile duct after a complaint of abdominal pain and jaundice was reported. Patient had originally been diagnosed with gastroesophageal reflux that had been attributed to her small size, poor development, and small weight gain. During her care in pediatrics, a genetic evaluation was solicited because of the following phenotypical findings: brachycephaly, oblique palpebral fissures, por language skills, and small size. At the Genetic institute in the Pontificia Universidad Javeriana the positive genetic findings are as follows: flat occiput, bilateral epicanthus, bilateral palpebral fissures, broad nasal bridge, microcephaly, hypertelorism, surgical correction of cleft palate, extremities with bilateral syndactyly in II and III toe, and bilateral shortening of the V finger. Parent comments that language skills had improved with cleft palate correction and that patient had experienced generalized seizures. We preformed a G band karyotype that found a ring chromosome 21. Noteworthy is that with present studies this is the second case reported of ring chromosome 21 with craniofacial abnormalities such as cleft palate.